The definition tool (Al) in Arabic is a phonological study - Naseem, Batoul Abbas (Al-Adab Journal, 2015)
)Al (the definition in the Arabic language ) Al( definition: is an important tool of the Arabic language، tools they deserve study، because many details of the specialist needs to know، and read in her comprehensive linguistic research, and this research sponsor a statement in these details.